Platoon Intensity of Connected Automated Vehicles: Definition, Formulas, Examples, and Applications - Yangsheng Jiang; Fangyi Zhu; Zhihong Yao; Qiufan Gu; Bin Ran (Journal of Advanced Transportation)
The strength of connected automated vehicles (CAVs) clustering, namely, platoon intensity, has an essential impact on the traffic capacity, safety, and stability of the mixed traffic flow with CAVs and human-driven vehicles (HDVs). This article proposes the definition, formulas, examples, analysis, and applications of CAV platoon intensity. Firstly, the CAV platoon intensity considering the maximum platoon size is defined, and its mathematical calculation method is developed. Secondly, the three types of value ranges for platoon intensity are discussed. Thirdly, the distribution characteristics of five types of time headways were proposed. Finally, the influence of CAV platoon intensity on the fundamental diagram and traffic safety of mixed traffic flow are analyzed from theoretical derivation and simulation evaluation, respectively. The result suggests the following: (1) According to the sensitivity analysis, an optimal platoon size of 5 vehicles was suggested for the CAV platoon; (2) The penetration rates and platoon intensity of CAVs can improve the capacity of mixed traffic flow, and the increase is gradually more significant; (3) The effect of the increase in platoon intensity on the capacity is not significant enough when the CAV penetration rate is low; (4) A higher platoon intensity is good for dissipating disturbances in the mixed traffic flow; and (5) CAV platoon intensity has a marginal impact on the characteristics of mixed traffic flow with the low penetration rate. It is noteworthy that a reasonable increase in platoon intensity can improve the traffic capacity and safety of mixed traffic flow.